A new species of Agenamyia Albuquerque (Diptera: Muscidae) from Colombia - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Fogaça, João M. (Zootaxa, 2024)
Agenamyia Albuquerque, 1953 is exclusive of the Neotropical region and is a poorly studied group. Here we described one new species from Colombia, namely Agenamyia diversa sp. nov. (type-locality: Garzón, Las Mercedes, Parque Natural Regional Cerro Páramo Miraflores), and present an updated identification key to segregate all the species, including color images and illustrations of male terminalia. The distribution of all species from Colombia is mapped.